The reuse of red brick powder as a filler in styrene-butadiene rubber. (10th July 2020) - Tang, Dawei; Zhang, Xuebin; Hu, Shusen; Liu, Xingyu; Ren, Xin; Hu, Jixiang; Feng, Yi
Abstract: The reasonable recycling of demolition wastes has attracted worldwide attention. Methods need to be investigated to reuse the waste materials such as broken bricks. This study added waste brick powder into the styrene-butadiene rubber (SBR) as one kind of filler in place of traditional fillers such as carbon black and white carbon black. The collected red brick fragments were broken into powder and filled in SBR to strengthen its mechanical property. Silane coupling agent KH-550 was utilized to improve the binding force between filler and rubber. The tensile property, conductivity and shore hardness of the vulcanized rubber was achieved. Results showed that the tensile strength of vulcanized SBR increased from 2.5 MPa to 3.6 MPa with the increase of brick powder filled in rubber. The Shore hardness increased from 43 to 53, while the volume resistance of the vulcanized rubber barely changed, maintaining around 5 kΩ cm. The rubber filled with modified brick powder showed better mechanical property than the unmodified. Economic and environmental profit were also evaluated. By applying red brick powder to polymer system, the problem of disposing demolition garbage can be eased and the cost will be markedly decreased in manufacturing polymer products. Graphical abstract: Image 1050 Highlights: Waste brick powder can be reused as a filler in Styrene-butadiene rubber. Modified brick powder has a better reinforcement property than the unmodified. The Shore hardness of vulcanized SBR increases with increasing brick powder. Economical cost can be saved sharply using brick powder as a filler in rubber.